Roadmap of internationalization : development and implementation of an entry strategy for the Portuguese Beachwear Company Miitik - Linnig, Johannes Martin (2017)
Miitik, a premium beachwear Start-up, seeks international growth to increase sales. Currently, the company mainly operates on the Portuguese market, but already gained some international experience by sporadically exporting to customers in Luxembourg and the United Kingdom. However, the Start-up is lacking a strategic approach in order to target international markets. Bearing this in mind, the company would like to find out about potential countries and is interested in a detailed entry strategy to overcome challenges small companies face in the process of internationalization. The thesis provides a deep study of relevant measures for the formulation of an entry strategy. Analyzing macro-economical factors helped to assess the potential of the chosen market Germany. The literature on internationalization suggests a four-step approach to develop an entry strategy. Based on the findings and the capabilities of the company, direct exports were selected as the most suitable entry mode. Further recommendations regarding the creation of brand awareness and distribution channels were drawn.